Personalized nutrition, microbiota, and metabolism: A triad for eudaimonia - Sarfraz, Muhammad Hassan; Shahid, Aqsa; Asghar, Samra; Aslam, Bilal; Ashfaq, Usman Ali; Raza, Hammad; Prieto, Miguel A.; Simal-Gandara, Jesus; Barba, Francisco J.; Rajoka, Muhammad Shahid Riaz; Khurshid, Mohsin; Nashwan, Abdulqadir J. (Frontiers in Molecular Biosciences, 2022)
During the previous few years, the relationship between the gut microbiota, metabolic disorders, and diet has come to light, especially due to the understanding of the mechanisms that particularly link the gut microbiota with obesity in animal models and clinical trials. Research has led to the understanding that no specific diet is suitable for people, due to the varying responses of individuals to dietary inputs. The variations are attributed to differences in the microbiome and host characteristics. In general, it is believed that the immanent nature of host-derived factors makes them difficult to modulate. However, diet can more easily shape the microbiome, potentially influencing human physiology through modulation of digestion, absorption, mucosal immune response, and the availability of bioactive compounds. Thus, diet could be useful to influence the physiology of the host, as well as to ameliorate various disorders. In the present study, we have described recent developments in understanding the disparities of gut microbiota populations between individuals and the primary role of diet-microbiota interactions in modulating human physiology. A deeper understanding of these relationships can be useful for proposing personalized nutrition strategies and nutrition-based therapeutic interventions to improve human health.